Pengaruh knowledge management terhadap kinerja karyawan bagian teknisi - Rizqi Setiawan; Tetra Hidayati; Ariesta Heksarini (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The   purpose   of   this   study   was   to   investigate   the   Effect   of Knowledge Management         which         consists         of Personal         Knowledge,         Job Procedure, and Technology on the Employee Performance of technicians at Media Nusantara Citra SKY VISION Samarinda. The tool that used for this analysis was multiple linear regressions. Based  on  the  results  of  multiple  linear  regressions  analysis  implied  the Knowledge   Management variable   that   consists   of Personal   Knowledge,   Job Procedure, and Technology had a positive effect and significant on the Employee Performance. Based on calculation on correlation of coefficient had indicated the value of 0.615 or 61.50% at the level of coefficient interval from 0.60 to 0.799, then Personal Knowledge,   Job   Procedure, and Technology have   strong   relationships   on   the Employee  Performance. The  value  on  determination  of  coefficient  was  0.378  or 37.8%. This implied that independent variables such as Personal Knowledge, Job Procedure, and  echnology in this study affect the employee performance amounted 37.8%. While  the  remaining  62.2%  influenced by  other  variables  that  were  not examined.